2018
DOI: 10.1530/erc-17-0476
|View full text |Cite
|
Sign up to set email alerts
|

HSD17B1 expression induces inflammation-aided rupture of mammary gland myoepithelium

Abstract: Hydroxysteroid (17-beta) dehydrogenase type 1 (HSD17B1) converts low-active estrogen estrone to highly active estradiol. Estradiol is necessary for normal postpubertal mammary gland development; however, elevated estradiol levels increase mammary tumorigenesis. To investigate the significance of the human HSD17B1 enzyme in the mammary gland, transgenic mice universally overexpressing human HSD17B1 were used (HSD17B1TG mice). Mammary glands obtained from HSD17B1TG females at different ages were investigated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
(81 reference statements)
1
9
0
Order By: Relevance
“…Accessed on date: February 2018) and a phase II trial started 2016 ( http://adisinsight.springer.com/drugs/800041929 ) . ∧ NSCLC: non-small cell lung cancer ∧∧ LAM: lymphangioleiomyomatosis 1 Perez Carrion et al ( 1994 ), 2 Arnold and Einspanier ( 2013 ), 3 Delvoux et al ( 2014 ), 4 Konings et al ( 2017 ), 5 Järvensivu et al ( 2018 ), 6 Husen et al ( 2006 ), 7 Saloniemi et al ( 2010 ), 8 Gargano et al ( 2015 ), 9 Soubhye et al ( 2015 ) 10 Day et al ( 2013 ), 11 Wang et al ( 2017 ), 12 BroŽic et al ( 2011 ), 13 Kikuchi et al ( 2014 ), 14 Purohit and Foster ( 2012 ), 15 Pautier et al ( 2017 ), 16 Palmieri et al ( 2017a ), 17 Palmieri et al ( 2017b ), 18 Pohl et al ( 2014 ), 19 Ma et al ( 2004 ), 20 Rose et al ( 2000 ), 21 Lindemann et al ( 2014 ), 22 Slomovitz et al ( 2015 ), 23 NCT00932152; 25 Lu et al ( 2017 ) . …”
Section: Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessed on date: February 2018) and a phase II trial started 2016 ( http://adisinsight.springer.com/drugs/800041929 ) . ∧ NSCLC: non-small cell lung cancer ∧∧ LAM: lymphangioleiomyomatosis 1 Perez Carrion et al ( 1994 ), 2 Arnold and Einspanier ( 2013 ), 3 Delvoux et al ( 2014 ), 4 Konings et al ( 2017 ), 5 Järvensivu et al ( 2018 ), 6 Husen et al ( 2006 ), 7 Saloniemi et al ( 2010 ), 8 Gargano et al ( 2015 ), 9 Soubhye et al ( 2015 ) 10 Day et al ( 2013 ), 11 Wang et al ( 2017 ), 12 BroŽic et al ( 2011 ), 13 Kikuchi et al ( 2014 ), 14 Purohit and Foster ( 2012 ), 15 Pautier et al ( 2017 ), 16 Palmieri et al ( 2017a ), 17 Palmieri et al ( 2017b ), 18 Pohl et al ( 2014 ), 19 Ma et al ( 2004 ), 20 Rose et al ( 2000 ), 21 Lindemann et al ( 2014 ), 22 Slomovitz et al ( 2015 ), 23 NCT00932152; 25 Lu et al ( 2017 ) . …”
Section: Drug Developmentmentioning
confidence: 99%
“…Accessed on date: February 2018) (Blake et al, 2017 ) . 1 Caron et al ( 1997 ), 2 Huang et al ( 2012 ), 3 Hu et al ( 2002 ), 4 Liu et al ( 2005 ), 5 Bair and Mellon ( 2004 ), 6 Nemoto et al ( 2000 ), 7 Fisher et al ( 1998 ), 8 Honda et al ( 1998 ), 9 Hakkarainen et al ( 2015 ), 10 Saloniemi et al ( 2010 ) and Järvensivu et al ( 2018 ), 11 Rantakari et al ( 2008 ), 12 Zhongyi et al ( 2007 ), 13 Baes et al ( 2000 ), 14 Shehu et al ( 2008 ), 15 Jokela et al ( 2010 ), 16 Shang et al ( 2002 ), 17 Driessen et al ( 2000 ) and Sahu et al ( 2015 ); 18 Li et al ( 2010 ) and Rauschenberger et al ( 2010 ); 19 Li et al ( 2010 ); Rauschenberger et al ( 2010 ), 20 Dickinson et al ( 2016 ), 21 Rantakari et al ( 2010 ); Kemilainen et al ( 2016 ); 22 Tang et al ( 2010 ), 23 Tang et al ( 2010 ), 24 Kim et al ( 2005 ), 25 Piekorz et al ( 2005 ), 26 Ishida et al ( 2007 ), 27 Mahendroo et al ( 1996 ), 28 Mahendroo et al ( 2001 ), 29 Dickinson et al ( 2016 ), 30 Qian et al ( 2001 ) and Tong et al ( 2005 ) . …”
Section: Drug Developmentmentioning
confidence: 99%
“… 5 This enzyme provides regulation in the final stages of active estrogen (estradiol) biosynthesis. 6 It has been reported that the activity of this enzyme increases the level of estrogen. It stimulates the development of breast cancer cells through cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…5,9 Therefore, this enzyme is a potential target in inhibiting the regulation of cancer cell development. [6][7][8][9] Several research projects are looking for candidate inhibitors that can block the process of estrogen biosynthesis through enzyme HSD17B1 inhibition. 4,9,10 There are several inhibitors with known activity (K m ) as HSD17B1 inhibitors, such as dihydrotestosterone (DHT): 32 AE 9 mM, and androstandione: 26 AE 9 mM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation